2009
DOI: 10.2139/ssrn.1364211
|View full text |Cite
|
Sign up to set email alerts
|

Information Sharing and Information Acquisition in Credit Markets

Abstract: Since information asymmetries have been identified as an important source of bank profits, it may seem that the establishment of information sharing will lead to lower investment in acquiring information. However, banks base their decisions on both hard and soft information, and it is only the former type of data that can be communicated credibly. We show that when hard information is shared, banks will invest more in soft, relationship-specific information. These will lead to more accurate lending decisions, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
13
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 8 publications
3
13
0
Order By: Relevance
“…Second, with regard to the connection of the findings with broad strands of the literature, it is reasonable to infer that the findings on financial activity are largely consistent with the stream of literature supporting the positive role of ISOs in stimulating financial access (Padilla & Pagano, 2000;Jappelli & Pagano, 2002, 2006Bennardo et al, 2015;Asongu et al 2017a, whereas the results on financial allocation efficiency are largely in line with the contrasting stream on the negatives of ISOs (Karapetyan & Stacescu, 2014a;Jappelli & Pagano, 2006;Karapetyan & Stacescu, 2014b;. It is important to note that this comparative emphasis in light of the extant conflicting literature is exclusively based on the significant findings from regressions related to financial activity relative to insignificant results pertaining to financial allocation efficiency.…”
Section: Discussion Of Resultssupporting
confidence: 71%
“…Second, with regard to the connection of the findings with broad strands of the literature, it is reasonable to infer that the findings on financial activity are largely consistent with the stream of literature supporting the positive role of ISOs in stimulating financial access (Padilla & Pagano, 2000;Jappelli & Pagano, 2002, 2006Bennardo et al, 2015;Asongu et al 2017a, whereas the results on financial allocation efficiency are largely in line with the contrasting stream on the negatives of ISOs (Karapetyan & Stacescu, 2014a;Jappelli & Pagano, 2006;Karapetyan & Stacescu, 2014b;. It is important to note that this comparative emphasis in light of the extant conflicting literature is exclusively based on the significant findings from regressions related to financial activity relative to insignificant results pertaining to financial allocation efficiency.…”
Section: Discussion Of Resultssupporting
confidence: 71%
“…The empirical literature is also broadly consistent on the position that such information asymmetry between lenders and borrowers can be alleviated through the establishment of information sharing offices that readily and timeously collect and exchange information on borrowers' characteristics in order to reduce adverse selection experienced by banks on the one hand and moral hazard from borrowers on the other (Brown et al, 2009;Djankov et al, 2007;Boateng et al, 2018). The studies broadly support the perspective that ISO enhances credit expansion as well as constitutes a relevant determinant of profitability and competition in the banking and insurance industry (Pagano & Jappelli, 1993;Padilla & Pagano, 2000;Brown & Zehnder, 2010;Karapetyan & Stacescu, 2014a, 2014b. However, there is another strand of the literature which posits that ISO may not engender the postulated theoretical appeals.…”
Section: Information Sharing and Banking/insurance Marketsupporting
confidence: 69%
“…These findings implied that the Saccos gather information from the institutions where loans were borrowed previously by the applicant before advancing a loan. In a study carried out in Tunisia on information sharing and information acquisition in the country's credit markets by Karapetyan and Stacescu (2010), it was established that information sharing provide more accurate lending decisions, provide higher welfare, which leads to an increased locus on relationship banking, and favor informationally opaque borrowers.…”
Section: Discussionmentioning
confidence: 99%
“…In a study carried out in Tunisia on information sharing and information acquisition in the country's credit markets by Karapetyan and Stacescu (2010), it was established that information sharing provide more accurate lending decisions, provide higher welfare, which leads to an increased locus on relationship banking, and favor informationally opaque borrowers. In a related review in Libya, McIntosh and Wydick (2014) observed that credit information systems first create a screening effect that advances risk evaluation of loan applicants, thereby raising portfolio quality, which, in turn, reduces rates of arrears.…”
Section: Introductionmentioning
confidence: 99%